Successful treatment of rotator cuff tear using Fascial Manipulation® in a stroke patient. Issue 3 (July 2017) - Pintucci, Marco; Simis, Marcel; Imamura, Marta; Pratelli, Elisa; Stecco, Antonio; Ozcakar, Levent; Battistella, Linamara Rizzo
Abstract: Rotator cuff tear is a common disease affecting patients after stroke. It's a cause of pain and dysfunction that may compromise normal stroke rehabilitation. For many cases there is still controversy between whether to use surgical or conservative intervention. Treatment for cuff tears range from physical therapy to surgery. This paper describes for the first time the effect of Fascial Manipulation ® (FM ® ) on rotator cuff tear in a post stroke patient. A 69 year old female stroke patient with full absence of distal components of the tendons of the rotator cuff, functional limitations on active movement of shoulder flexion and abduction of the left arm and perceived pain scored 10/10 on the Visual Analogic Scale, was assessed and treat with one session of FM ® A basic theory that explains the healing results of FM ® is that mechanoreceptors, such as spindle cells and other receptors, are located in the deep fascia and activated when movement are performed. Increased viscosity of the deep fascia and muscles due to increased viscosity of hyaluronic acid (HA) molecules prevents the normal gliding of fascia during movement inhibiting normal proprioception and muscle function.